Emergency department visits and hospitalizations among patients with sickle cell disease in illinois, 2016–2020. (2nd January 2023) - Barriteau, Christina M.; Feinglass, Joe; Kayle, Mariam; VonAchen, Paige; Liem, Robert I.; Badawy, Sherif M.; Kan, Kristin
Abstract: Sickle cell disease (SCD) state level surveillance data are limited. We performed a retrospective review of emergency department (ED) visits and hospitalizations from individuals with SCD in Illinois (2016–2020) using the Illinois Health and Hospital Association's Comparative Health Care and Hospital Data Reporting Services. There were 48, 094 outpatient ED visits and 31, 686 hospitalizations. Most visits (67%) occurred in Cook County, were covered by public insurance (77%) and were from individuals with medium high (40.3%) or high (36.1%) poverty levels. SCD healthcare utilization remains high and surveillance data may inform SCD program development and resource allocation at the state level. Abbreviations CDC Centers for Disease Control and Prevention ED Emergency Department FDA Food & Drug Administration ICD International Classification of Diseases IL Illinois SCD Sickle cell disease